Survival and Success of Dental Implants in Patients with Autoimmune Diseases: a Systematic Review - Emil Hyldahl; Klaus Gotfredsen; Anne Marie Lynge Pedersen; Simon Storgård Jensen (Stilus Optimus, 2024)
Objectives: The purpose of this systematic review is to disclose the impact of autoimmune diseases and their medical treatment on dental implant survival and success. Material and Methods: A literature search was conducted using MEDLINE (PubMed), The Cochrane Library and Embase up to December 6th, 2021. Any clinical study on patients with an autoimmune disease in whom implant therapy was performed was eligible. The quality of included studies was assessed using the Newcastle-Ottawa Scale. For each autoimmune disease group, data synthesis was divided into three groups: 1) overall results of the autoimmune disease, 2) overall results of corresponding control groups and 3) overall results of the autoimmune disease with a concomitant autoimmune disease (a subgroup of group 1). Descriptive statistics were used. Results: Of 4,865 identified articles, 67 could be included and mainly comprising case reports and retrospective studies with an overall low quality. Implant survival rate was 50 to 100% on patient and implant level after a weighted mean follow-up of 17.7 to 68.1 months. Implant success was sporadically reported. Data on immunosuppressive medication were too heterogeneously reported to allow detailed analysis. Conclusions: Overall, a high implant survival rate was reported in patients with autoimmune diseases. However, the identified studies were characterized by a low quality. No conclusions could be made regarding implant success and the effect of immunosuppressants due to heterogeneous reporting.